Clinical, Radiological, and Molecular Findings in Cases with TRAPPopathies - Ayça Dilruba Aslanger; Esma Sengenç; Emrah Yücesan; Beyza Göncü; Akın İşcan; Gözde Yeşil Sayın (Çocuk Dergisi)
Objective: Pathologies occurring in Transport Protein Particles (TRAPP) involved in vesicular traffic are rare diseases called TRAPPopathies. The aim of this study was to present a case series of TRAPPopathies, to describe the clinical and molecular findings, and additionally to review our cases together with other cases reported from Turkiye. Materials and Methods: Patients with neurological findings such as microcephaly, epilepsy, muscular dystrophy, and intellectual disability who were referred to Bezmialem Vakıf University, Faculty of Medicine, Department of Medical Genetics between March 2018 and March 2020 were reviewed for this study. Patients with pathogenic variants in genes with TRAPP complex family with known phenotype or not yet associated any human disease were included in the study. Clinical, radiological, and molecular findings obtained by whole exome sequences of cases were re-evaluated. Results: Molecular analysis revealed homozygous c.454+3A>G p.(?) variant in TRAPPC4 (NM_016146.5) gene in Case 1 with neuromotor retardation, intractable seizures, postnatal microcephaly, and cerebralcerebellar atrophy, homozygous novel c.57C>G p.(Try19Ter) variant in TRAPPC6B (NM_001079537.1) in Case 2 with epilepsy, postnatal microcephaly, severe neuromotor retardation, and autism, and homozygous c.2938G>A p.(Gly980Arg) variant in TRAPPC11 (NM_021942.5) gene in Case 3 with muscular dystrophy, cataract, neuromotor retardation, and microcephaly. Conclusion: This study showed that newly identified genes in TRAPPopathies are responsible for microcephaly, developmental delay, epilepsy, intellectual disability, cerebral-cerebellar atrophy, and autism. Although the genes in the TRAPP family work independently of each other, the diseases in this group are called TRAPPopathies because their phenotypes overlap. The aim of our study was to discuss the clinical findings and to summarize the mutation profile of the genes in the TRAPP family in Turkiye.